The Mediating Role of Employee Engagement between Team and Co-worker Relation, Work Environment, Training and Development and Employee Performance - Saengchai, Sakapas (International Journal of Psychosocial Rehabilitation, 2019)
Employee performance has been the major issue now a day in the manufacturing organization of Indonesia. Management is giving more focus to obtain more performance through adopting new technologies but no avail. The current study discussed this issue how to enhance employees’ performance. The main aim of this study is to examine the mediating role of employees’ engagement between team and co-worker relations, training and development, work environment and lastly with employee’s performance. This quantitative study used cross-sectional design. Population is selected from the Indonesian Manufacturing industry. Adapted questionnaire would be used to collect the response from the respondents. 300 questionnaires distributed to get the data. PLS (AMOS) 3.0 Version is used to do data analyze. The findings of the study show that employees’ engagement has significant relation between TCR, TD and WE and EP. The conclusion of the study shown that manufacturing company especially the food industry can use to maintain the employee’s performance, by paying more attention to training and development, sustaining good relation with team and co-workers and work environment that the employees get, in order to achieve business objectives and then raise competitive advantages in Indonesian manufacturing industry.